An ethnobotanical study on wild plants used by Tibetan people in Gyirong Valley, Tibet, China - Chang-An Guo; Xiaoyong Ding; Huabin Hu; Yu Zhang; Huizhao Yang; Yuhua Wang (BMC, 2022)
Abstract Background Gyirong Valley known as the "Back Garden of the Himalayas" is located in the core area of the Everest National Nature Reserve. It is also one of the important ports from ancient Tibet to Kathmandu, Nepal, since ancient times. Over the years, the Tibetans of Gyirong had accumulated sufficient traditional knowledge about local plant resources. However, there is almost no comprehensive report available on ethnobotanical knowledge about the local people. The purposes of this study were to (1) conduct a comprehensive study of wild plants used by Tibetan people in Gyirong Valley and record the traditional knowledge associated with wild useful plants, (2) explore the influence of Tibetan traditional culture and economic development on the use of wild plants by local people, and (3) explore the characteristics of traditional knowledge about wild plants of Tibetans in Gyirong. Methods Ethnobotanical data were documented through free listings, key informant interviews and semi-structured interviews during fieldwork. The culture importance index and the informant consensus factor index were used as quantitative indices. Results In total, 120 informants (61 women and 59 men) and 3333 use reports and 111 wild plant species belonging to 39 families and 81 genera were included. These use reports were then classified into 27 categories belonging to three major categories. The use category that contained the most plant species was edible plants (62), followed by medicinal plants (32) and economic plants (22), and other uses (71). Plants with high CI included Allium prattii, Neopicrorhiza scrophulariiflora, Gymnadenia orchidis, Rhododendron anthopogon and Fritillaria cirrhosa. Thirty-six species of plants in the catalog of Gyirong and Yadong were the same, but only 17 species were the same in Gyirong and Burang. There were only 11 overlapping species between all the three regions. Conclusion Tibetans of Gyirong have rich and unique knowledge about plant use, and wild edible and medicinal plants play an important role in the nutrition and health protection of local people. However, traditional knowledge is slowly being lost and is being hit by modern tourism. In the future, more attention needs to be paid to the important role of traditional knowledge in biodiversity conservation.